Regulation of the cardiac sodium/bicarbonate cotransporter by angiotensin II : Potential Contribution to structural, ionic and electrophysiological myocardial remodelling - Aiello, Ernesto Alejandro (2013)
The sodium/bicarbonate cotransporter (NBC) is, with the Na+ /H+ exchanger (NHE), an important alkalinizing mechanism that maintains cellular intracellular pH (pHi). In the heart exists at least three isoforms of NBC, one that promotes the co-influx of 1 molecule of Na+ per 1molecule of HCO3- (electroneutral isoform; nNBC) and two others that generates the co-influx of 1 molecule of Na+ per 2 molecules of HCO3- (electrogenic isoforms; eNBC). In addition, the eNBC generates an anionic repolarizing current that modulate the cardiac action potential (CAP), adding to such isoforms the relevance to modulate the electrophysiological function of the heart. Angiotensin II (Ang II) is one of the main hormones that regulate cardiac physiology. The alkalinizing mechanisms (NHE and NBC) are stimulated by Ang II, increasing pHi and intracellular Na+ concentration, which indirectly, due to the stimulation of the Na+/Ca2+ exchanger (NCX) operating in the reverse form, leads to an increase in the intracellular Ca2+ concentration. Interestingly, it has been shown that Ang II exhibits an opposite effect on NBC isoforms: it activates the nNBC and inhibits the eNBC. This inhibition generates a CAP prolongation, which could directly increase the intracellular Ca2+ concentration. The regulation of the intracellular Na+ and Ca2+ concentrations is crucial for the cardiac cellular physiology, but these ions are also involved in the development of cardiac hypertrophy and the damage produced by ischemia-reperfusion, suggesting a potential role of NBC in cardiac diseases.